Assessment in speech-language pathology : a resource manual - Shipley, Kenneth G.; McAfee, Julie G. (San Diego, CA : Plural Publishing, Inc., 2021)
'This thoroughly updated sixth edition of the best-selling text Assessment in Speech-Language Pathology remains an invaluable resource for instructors, students, and clinicians. The book covers the diagnosis, evaluation, and treatment of a wide range of communication disorders in adults and children. This one-of-a-kind manual provides a comprehensive package of reference materials, explanations of assessment procedures, practical stimulus suggestions, and hands-on worksheets and screening forms. The highly practical resource is separated into four easy-to-navigate sections: Part I highlights preparatory considerations; Part II includes procedures and materials for obtaining, interpreting, and reporting assessment information; Part III provides materials and suggestions for assessing communicative disorders. Part IV presents a quick-reference section, providing information on hearing considerations, medical diagnoses, and caregiver handouts'--Publisher's description.
Foundations of assessment -- Multicultural considerations -- Obtaining preassessment information -- Reporting assessment findings -- Assessment procedures common to most communicative disorders -- Assessment of speech sound disorders -- Assessment of spoken language in children -- Assessment of written language -- Assessment of selective mutism -- Assessment for autism spectrum disorder and social communication disorder -- Assessment for augmentative or alternative communication (AAC) -- Assessment of stuttering and cluttering -- Assessment of voice and resonance -- Assessment of acquired neurogenic language disorders -- Assessment of acquired neurogenic speech disorders -- Assessment of dysphagia -- Hearing considerations -- Medical diagnoses associated with communicative disorders.
Includes bibliographical references and index.
Description based on online resource; title from resource home page (ProQuest Ebook Central, viewed April 23, 2021).
WorldCat record variable field(s) change: 650
Keywords: Communicative disorders -- Diagnosis; Speech disorders -- Diagnosis; Language disorders -- Diagnosis; Needs assessment; Communication Disorders -- diagnosis; Speech-Language Pathology -- methods; Needs Assessment; Analyse des besoins; needs assessment; Communicative disorders -- Diagnosis; Language disorders -- Diagnosis; Speech disorders -- Diagnosis; Electronic books; Electronic books